Evaluation of long-term corrosion durability and self-healing ability of scratched coating systems on carbon steel in a marine environment - 赵霞 陈长伟 徐玮辰 朱庆军 戈成岳 侯保荣 (Chinese journal of oceanology and limnology, 2017)
Defects in protective-coating systems on steel surfaces are inevitable in practical engineering applications. A composite coating system, including a primer, middle coat and topcoat, were used to protect carbon steel from corrosion in a marine environment. Two environmental additives, glass fibers and thiourea, were applied in the middle coat to modify the coating system. The long-term corrosion durability and self-healing ability of the scratched coating system were evaluated by multiple methods. Results of the electrochemical technologies indicated that the coating system that contained 0.5 wt.% fibers and 0.5 wt.% thiourea presented good corrosion protection and self-healing for carbon steel when immersed in 3.5% NaCl for 120 d. Evolution of localized corrosion factors with time, as obtained from the current distribution showed that fibers combined with thiourea could inhibit the occurrence of local corrosion in scratched coating systems and retarded the corrosion development significantly. Surface characterization suggested that adequate thiourea could be absorbed tmiformly on fibers for a long time to play an important role in protecting the carbon steel. Finally, schematic models were established to demonstrate the action of fibers and thiourea on the exposed surface of the carbon steel and the scratched coating system in the entire deterioration process.